High-Fat-High-Fructose Diet Decreases Hippocampal Neuron Number in Male Rats - Inggita Kusumastuty; Frinny Sembiring; Sri Andarini; Dian Handayani (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Consumption of foods and drinks high in energy, fat, and/or sugar beyond the recommended quantities can cause obesity, which triggers the incidence of brain nerve cell death related to oxidative stress, high levels of tumor necrosis factor (TNF)-α and triglycerides, and low high-density lipoprotein (HDL) levels. Progressive nerve cell death causes decreasing cognitive performance. This study aims to prove that an American Institute of Nutrition committee in 1993 (AIN-93M) diet modified with high-fat-high-fructose (HFHF) can decrease the number of hippocampal neurons. A decrease in the number of hippocampal neurons indicates progressive nerve cell death.METHODS: An experimental study using a post-test control group design was carried out using male Sprague Dawley rats. Samples were selected using simple random sampling to divide them into two groups, Group I was AIN-93M-modified HFHF diet (n=14) and Group II was AIN-93M standard (n=16). The number of visible neurons was measured in the hippocampus area of Sprague Dawley rats’ brains, stained with haemotoxylin and eosin (H&E) and scanned under 400x magnification. Neurons were counted in 10 visual fields using the